2020
DOI: 10.1136/bmjopen-2019-035951
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-urgent visits to the emergency department in a tertiary care centre, western Saudi Arabia: cross-sectional study

Abstract: ObjectivesTo explore magnitude and factors associated with non-urgent visits to the emergency department (ED) in a tertiary care centre, western Saudi Arabia.DesignA cross-sectional study.SettingED of a tertiary care hospital in western Saudi Arabia.Participants400 patients, both men and women.InterventionsAn interview-based questionnaire was administered to a consecutive sample of patients who visited the ED during morning shifts, where primary healthcare centres (PHCs) and outpatient clinics were available.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 22 publications
6
31
10
Order By: Relevance
“…15,30,[34][35][36][37] The acuity level in this study mostly features less urgent cases, which accords with other studies. 25 The chronic diseases, reported in this study, are lower than that of Al-Otmy etal. 25 One of the possible explanations might be due to that all public hospitals in Saudi Arabia have to accept all patients visiting the ED, which encourage patients to bypass the primary care centers, ignoring nature of ED services that must be for life saving conditions.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…15,30,[34][35][36][37] The acuity level in this study mostly features less urgent cases, which accords with other studies. 25 The chronic diseases, reported in this study, are lower than that of Al-Otmy etal. 25 One of the possible explanations might be due to that all public hospitals in Saudi Arabia have to accept all patients visiting the ED, which encourage patients to bypass the primary care centers, ignoring nature of ED services that must be for life saving conditions.…”
contrasting
confidence: 57%
“…25 The chronic diseases, reported in this study, are lower than that of Al-Otmy etal. 25 One of the possible explanations might be due to that all public hospitals in Saudi Arabia have to accept all patients visiting the ED, which encourage patients to bypass the primary care centers, ignoring nature of ED services that must be for life saving conditions. Previous literature has discussed different reasons for seeking ED visits.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Similar findings were observed both nationally and internationally. 19 , 20 For example, in Riyadh—Saudi Arabia—79.9% of patients were dissatisfied with waiting time and 44% of patients felt neutral about the availability of requested lab results. 21 , 22 Such issues may be exacerbated by the high demands of such services due to the increasing rates of chronic diseases in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research of one tertiary hospital in SA, 78.5% of visits to the ER were of non-urgent cases [ 5 ]. Another research which looked into three tertiary hospitals in SA found that non-urgent cases comprised 53% of all ER visits and examining paediatric ER visits specifically, non-urgent cases ranged between 35.9 and 59.5% [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%